EMOSI KONSUMEN DALAM MENDUKUNG KEPUASAN PEMBELIAN SECARA ONLINE DI MASA PANDEMI COVID 19 - Lesy Cornella; Dedi Rianto Rahadi (Jurnal Manajemen dan Profesional, 2020)
Emotions are things that cannot be measured from human behavior, because every human being must have emotions, both negative emotions and emotions. At this time, many considerations are made when buying an item, one of which is the emotional factor. Consumer emotions have become unstable due to the plague that hit Indonesia, namely the Covid 19 outbreak. This pandemic has caused several activities to stop, one of which is the ban on crowding. Currently, purchases are mostly made online, as evidenced by the increasing number of online shopping application users. Even though the purchase is made online, satisfaction is still considered in order to maintain a good customer relationship. The study used a qualitative method of interviewing. By using this method, it is hoped that the research will be more focused and the results obtained are in accordance with the facts that occur. The results showed that consumer emotions were one of the supporting factors for online purchase satisfaction during the Covid 19 pandemic.